Półka literacka 2011 - Nęcka, Agnieszka (Postscriptum Polonistyczne, 2020)
The article presents the most important and the most interesting prose and poetry works published in 2011. Most of them were written by well known authors. Those that particularly deserve mentioning are Saturn. Czarne obrazy z życia mężczyzn Goya by Jacek Dehnel, Bornholm, Bornholm by Hubert KlimkoDobrzaniecki, Książka by Mikołaj Łoziński, Ziarno prawdy by Zygmunt Miłoszewski, Włoskie szpilki by Magdalena Tulli and Drwal by Michał Witkowski. In poetry, the works by Konrad Góra (Pokój widzeń), Szczepan Kopyt (Buch), Marta Podgórnik (Rezydencja surykatek) and Eugeniusz TkaczyszynDycki (Imię i znamię) were enthusiastically received by readers. Apparently, year 2011 confirmed quite stabile preferences of the readers, which resulted in appreciation above all such publications that grounded in ‘middle literature’ tended to hybrid form, transgression of literary genres, artistic expressiveness. Works that received the warmest readers’ response were those dedicated to the identity problems or facing the demons of the past.